OP63 Estimating and communicating prognosis in palliative care: a cross-sectional survey among physicians in the southwest region of the netherlands. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Engel, M; Van der Ark, A; Tamerus, R; van der Heide, A
Abstract : Background: Advance care planning is important for patients with an advanced illness and a limited life expectancy. We explored experiences from physicians from different settings with estimating and communicating patients' poor prognosis. Methods: A survey study was performed in 2017 in the Southwest region of the Netherlands among a random sample of physicians working in primary care, hospitals and nursing homes (n=2212). Results: 547 physicians participated: 259 general practitioners (GP's), 205 hospital physicians (HP's) en 83 nursing home physicians (NHP's). In total, 61.1% stated that they can adequately estimate if a patient will die within a year; 66.7% stated that they can adequately estimate a life expectancy of less than three months and 76.1% a life expectancy of less than a week. When a patient is estimated to have a prognosis of less than one year, 75.0% of all physicians indicate that they always/often discuss their wishes for treatment and care. For patients with an estimated prognosis of less than three months, 85.9% of HP's discuss patients' wishes, compared to 96.1% of GP's and 91.6% of NHP's. After hospital admission of patients with a limited life expectancy, 29.0% of GP's and 16.9% of NHP's indicate that they always/often receive adequate information from HP's about patients' wishes. Conclusion: The majority of physicians indicate that they can adequately estimate a patient's limited life expectancy and that they tend to discuss patients' wishes if they have a poor prognosis. Information transfer concerning patients' wishes for treatment and care can be improved.